EPISTEMOLOGICAL DISCOURSE: ISLAMIZATION AND INTEGRATION PARADIGMS OF ISLAMIC SCIENCE - Taufiqurrahman (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2020)
This study discusses the paradigm of islamization and integration of science in discourse of epistemology as a tradition of islamic thought, to initiate a conceptual islamization of science. The method used was literature study with a historical approach to observe heuristic aspects, source criticism, and hypotheses. The Islamization of science can be seen from the methods used in a pluralistic, valid, and comprehensive manner, it is considered to exist if it is connected hierarchically as a multidimensional reality. The linkages of knowledge in Islam is an important aspect in Islamic epistemology, where the seeking for knowledge itself is not only an obligation, it is even a form of worship and is related to the values of al-Quran. The integration of Islamic science is a accommodation and absorption of islamic values in general science, as a reintroduction of scientific disciplines into the framework of Islam and the dissemination of Islamic science.